2013
DOI: 10.1111/ctr.12246
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a barrier to living kidney donation: a center‐based analysis

Abstract: Obesity may be a frequent barrier to living kidney donation, directly leading to exclusion as a potential kidney donor in about one in five instances. Successful weight loss leading to donation appears to be infrequent, suggesting need to address obesity in the donor population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…This is obviously not representative for the population that is undergoing kidney transplantation and is experiencing renal IRI. Overweight, comorbidities, old age, gender and the use of medication can all interfere with the effects of studied methods to ameliorate renal IRI [ 112 , 113 ]. Another limitation of animal experiments may be the use of warm ischemia models to mimic transplantation induced IRI [ 30 , 31 , 71 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is obviously not representative for the population that is undergoing kidney transplantation and is experiencing renal IRI. Overweight, comorbidities, old age, gender and the use of medication can all interfere with the effects of studied methods to ameliorate renal IRI [ 112 , 113 ]. Another limitation of animal experiments may be the use of warm ischemia models to mimic transplantation induced IRI [ 30 , 31 , 71 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also emphasises the need to address obesity in the potential donor population. 56 Ensuring potential donors know at the time a relative or friend is diagnosed with renal disease that a high BMI will prevent donation and offering weightloss support at this stage will not only improve the health of potential donors, but also increase the likelihood of them being suitable for donation if this is something they wish to pursue in the future. Engaging with weightloss in advance of a possible kidney donation will help clinicians assess if the weightloss is sustainable, and likely to be maintained after donation.…”
Section: Future Workmentioning
confidence: 99%
“…Morbid obesity is projected to have a significant impact on the number of suitable live donors available in the future [4][5][6]. Case reports of BS for a potential OLKD prior to donation have only been published two times to our knowledge but has likely been performed many more times [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Mandelbrot et al reported that of the transplant centers surveyed, 52% have a BMI cutoff of 35 kg/m 2 [4]. Others have suggested that 22% of potential live donors were ineligible due to high BMI [5]. Currently, more than one-third of adults in the United States are obese [6].…”
Section: Introductionmentioning
confidence: 99%